Relevance of Tagore’s Thought of Child Education to Current Educational Policy in Bangladesh: An Analysis - Khatun, Morjina (The Jahangirnagar Review Part-C, 2025)
Rabindranath Tagore presented a comprehensive model of Education, which can be called an alternative education plan to the traditional education system for the Indian subcontinent. The basis of his educational philosophy is Indian Philosophy, Religion, and Art. To understand his educational philosophy, the metaphysical aspect of his concept of Universal Man first be understood. The idea of this Universal Man should be achieved in the individual by harmony between the universal ideas of society, culture, and state. Tagore spoke of realizing man's inner quality through Education and connecting Education with all experiences. Thus the individual can connect with the Universal through Education. The human development effort is a prominent feature of his philosophy of Education, as he wanted to turn people into human resources through Education. The origin of Tagore's rural education program centered on His concept of child education. He built his institution in a lush green environment of the countryside for the normal mental development of children. Considering Education as an essential part of life, stimulating the child with the exercise of senses, nature observation, and constructive activities was the main idea of Tagore's idea of child education. His method strongly emphasized the positive and innovative parts of education and was synthetic for ensuring that children's personalities were properly integrated. So, this paper will consider the question ‘why Tagore’s thought of child education policy is relevant for the Bangladeshi education policy making’ to argue that, Tagore's educational philosophy paved the way for children to become free adults, which is still relevant today. It will also argue that children learn to recognize nature through recreational activities when they bond with nature in an open setting. Through joyful learning, they can explore a new universe. The current educational system of Bangladesh can be saved from anarchy and deterioration by addressing insights of pioneers like Rabindranath's initiatives in child education.